INDEKS KEPUASAN MASYARAKAT ( IKM ) PELAYANAN KTP DI UNIT PELAYANAN SATU PINTU KECAMATAN BAMBANGLIPURO - , Deni Ngajis Hartono, SSTP; , Dr. Nunuk Dwi Retnandari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
There are many cases appear in the society when we talk about public services. People are complaining because of they are often faced with uncertainty of certain affair and the regulation and procedure of public service that is tended to be complex. Long service procedure often makes the people using the service to feel tricked. Even though the people are following the rules stated, it needs much time. This is causing bad impact towards bureaucracy official bad attitudes in giving public service, so that it causes people trust crisis towards the government. The aim of this research is to find out the service quality and to find out factors that become obstacle in increasing the service quality related with the implementation of Regulation Number 32 Year of 2004 about Local Government. With the implementation of Regulation Number 32 Year of 2004, it is hoped that there is enhancement of government administration done by bureaucracy officers in becoming transparent and accountable. The officers that function is as the public servant have to be oriented toward the service that is satisfying and positioning the people in the place that have to be served. In fulfilling the demand toward people requirement and creating officers who are able to serve the people, it requires mental attitude alteration from the bureaucracy officers that is the alteration of thinking pattern and attitude pattern. The alteration has to be started from the leader work unit to all staff/subordinates. This research is qualitative descriptive analysis with case approach. Subject of this research is the bureaucracy officers giving public service in the Subdistrict of Bambanglipuro. The data collection in this research is conducted using interview technique, observation, documentation research and survey or questionnaire. From the research result and the data processing, it is found that the IKM result is 73,99, from the result it can be concluded that Society Satisfaction Index towards the service quality for Resident ID in the Single Door service of Subdistrict of Bambanglipuro is in good category. Factors that become obstacle in increasing the service quality in the Subdistrict of Bambanglipuro are: a. Factor of rule that become the service work platform is not guided the officers b. Factor of awareness of the officials and stuff in the service area is minimum c. Factor of organization that is the instrument and system which are enable to run the service activity mechanism to run minimum d. Factor of skill of the officers that is low e. Factors of tool and infrastructure which are minimum Then the forwarding steps which have to be conducted by the bureaucracy personells are to increase those five factors which are becoming obstacle/constrants in increasing the service.